2017
DOI: 10.1080/10410236.2017.1351278
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Disaster Communication and Social Media: Mixed-Method Systematic Review

Abstract: This mixed-method evidence synthesis drew on Cochrane methods and principles to systematically review literature published between 2003 and 2016 on the best social media practices to promote health protection and dispel misinformation during disasters. Seventy-nine studies employing quantitative, qualitative, and mixed methods on risk communication during disasters in all UN-languages were reviewed, finding that agencies need to contextualize the use of social media for particular populations and crises. Socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…Inevitably, disaster communication exists within a larger disaster information environment, compelling communicators to monitor and interact with this environment (Savoia et al, 2017). An increasing number of studies highlight the impact that news media can have on public perceptions and behaviors in crises (Eckert et al, 2018;Parmer et al, 2016;Westerman et. al., 2014), demonstrating its potential to be leveraged for its broad public reach and familiarity (Littlefield & Quenette, 2007;Reynolds & Seeger, 2005).…”
Section: Navigating the Disaster Information Environmentmentioning
confidence: 99%
“…Inevitably, disaster communication exists within a larger disaster information environment, compelling communicators to monitor and interact with this environment (Savoia et al, 2017). An increasing number of studies highlight the impact that news media can have on public perceptions and behaviors in crises (Eckert et al, 2018;Parmer et al, 2016;Westerman et. al., 2014), demonstrating its potential to be leveraged for its broad public reach and familiarity (Littlefield & Quenette, 2007;Reynolds & Seeger, 2005).…”
Section: Navigating the Disaster Information Environmentmentioning
confidence: 99%
“…In a parallel manner, given that we had fewer media outlets than initially planned, we chose three for the United States, including two that are ideologically opposed (CNN and Fox News) as well as a news outlet which not very politically inclined (Huffington Post). This heterogeneous sample of countries, with an overrepresentation of West African countries' media outlets, is justified by our attempt to counteract an ethnocentric bias in the academic field of health communication and social media, which often neglects the Southern hemisphere, including Africa (Eckert et al 2018). The dataset eventually included over 14 million Facebook comments.…”
Section: Data Extractionmentioning
confidence: 99%
“…However, efficacy information, encouraging self-efficacy and response efficacy that lead to appropriate emergency response (Reynolds & Seeger, 2005), was found to be insufficient in the same study (Vos & Buckner, 2016). A recent systematic review of health-related disaster communication and social media (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) (Eckert et al 2017), further revealed that: 1) social media, as public communication tools, have yet to become routine practice in government health agencies;…”
Section: Theoretical Underpinnings: the Rams Frameworkmentioning
confidence: 99%